Predictors of a high incidence of opportunistic infections among HIV-infected children receiving antiretroviral therapy at Amhara regional state comprehensive specialized hospitals, Ethiopia: A multicenter institution-based retrospective follow-up study - Mekonnen, Gebrehiwot Berie; Birhane, Binyam Minuye; Engdaw, Melaku Tadege; Kindie, Wotetenesh; Ayele, Amare Demsie; Wondim, Amare (Frontiers in Pediatrics, 2023)
Introduction: Globally, opportunistic infections are the leading causes of morbidity and mortality among HIV-infected children, which contributes to more than 90% of HIV-related deaths. In 2014, Ethiopia launched and started the test and treat strategy aiming to reduce the burden of opportunistic infections. Despite this intervention, opportunistic infections continue to be a serious public health issue with limited evidences on their overall incidence among HIV-infected children in the study area. Objective: The study was aimed to assess the incidence of opportunistic infections and its predictors among HIV-infected children on antiretroviral therapy in Amhara Regional State Comprehensive Specialized Hospitals, 2022. Methods: A multicenter institution-based retrospective follow-up study was conducted among 472 HIV-infected children on antiretroviral therapy at Amhara Regional State Comprehensive Specialized Hospitals from May 17 to June 15, 2022. Children on antiretroviral therapy were selected using simple random sampling technique. The data were collected using national antiretroviral intake and follow-up forms through the KoBo Toolbox. STATA 16 was used for data analyses, and Kaplan-Meier was used to estimate opportunistic infection-free survival probability. Both bi-variable and multivariable Cox-proportional hazard model was employed to identify significant predictors. A P-value ? 0.05 was used to declare statistical significance. Results: A total of 452 child records with completeness rate of 95.8% were included and analyzed in the study. The overall incidence of opportunistic infections among children on ART was 8.64 per 100 person-years observation. Having CD4 cell count below threshold [AHR: 2.34 (95% CI: 1.45, 3.76)], anemia co-morbidity [AHR: 1.68 (95% CI: 1.06, 2.67)], ever had fair and poor ART drug adherence [AHR: 2.31 (95% CI: 1.47, 3.63)], ever not taking tuberculosis preventive therapy [AHR: 1.95 (95% CI: 1.27, 2.99)], and had not initiated antiretroviral therapy within seven days of HIV diagnosis [AHR: 1.82 (95% CI: 1.12, 2.96)] were the predictors. Conclusion: The incidence of opportunistic infections was high. CD4 cells below the threshold, ever had fair and poor adherence to antiretroviral therapy, anemia co-morbidity, ever not taking tuberculosis preventive therapy, and not initiated antiretroviral therapy within seven days of HIV diagnosis were significant predictors for the incidence of opportunistic infections.